EL CINE COMO MEDIO DE COMUNICACIÓN SOCIAL. LUCES Y SOMBRAS DESDE LA PERSPECTIVA DE GÉNERO - Dra. Beatriz MORALES ROMO (Fonseca, Journal of Communication, 2023)
This article includes studies cinema as a social mass media, in relation to the influence it exerts on children and young people. From different aspects of the cinema, we deep in its role as transmitter of stereotypes, with special attention to the gender perspective. The methodology used has been both, quantitative and qualitative. On the one hand, a survey of 251 students of various university degrees has been applied and, on the other hand, in-depth interviews have been conducted with experts, and the 20 best-selling romantic films of the first decade of the 21st century have been studied through analysis sheets